La majorité oubliée: le rôle des femmes à Montréal au 19e siècle - Cross, D. Suzanne (Les femmes dans la société québécoise, 1977)
Keywords: Femmes

L'histoire des femmes au Québec depuis quatre siècles - Collectif Clio (Le Jour, 1992)
Keywords: Femmes

Les femmes et le vote au Bas-Canada, 1791-1849 - Picard, Nathalie (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Élections

Les femmes et le vote au Bas-Canada de 1792 à 1849 - Picard, Nathalie (Université de Montréal, 1992)
Keywords: Femmes; Élections

Mère Gamelin, femme de compassion (s.é., 1984)
Keywords: Communautés religieuses; Soeurs de la Providence; Tavernier; Émilie (Gamelin; Émilie)

La femme au coeur attentif: mère Gamelin - Nadeau, Eugène (Providence Montréal, 1969)
Keywords: Communautés religieuses; Soeurs de la Providence; Tavernier; Émilie (Gamelin; Émilie)

Par le chemin du roi une femme est venue - Duval, Germaine (Bellarmin, 1982)
Keywords: Communautés religieuses; Durocher; Eulalie; Soeurs des Saints Noms de Jésus et de Marie

Madame James McGill (1747-1818): Marie-Charlotte Guillimin, ou, La vie d'une femme mondaine à Montréal au dix-huitième siècle - Tanguay, Lynda (Université McGill, 1993)
Keywords: Bourgeoisie; McGill; James

Women and Technological Change in Nineteenth Century Montreal - Bradbury, Bettina (Women, Work and Place, 1994)
Keywords: Femmes

Quebec Women: a History - Collectif Clio (Women's Press, 1987)
Translators: _:n14097
Keywords: Femmes

The Neglected Majority: The Changing Role of Women in 19th Century Montreal - Cross, D. Suzanne (The Canadian City. Essays in Urban History, 1977)
Keywords: Femmes

The Neglected Majority: The Changing Role of Women in Nineteen Century Montreal - Cross, D. Suzanne (The Social Development of Canada - Readings, 1983)
Keywords: Femmes

The Neglected Majority: The Changing Role of Women in 19th Century Montreal - Cross, D. Suzanne (The Neglected Majority: Essays in Canadian Women's History, 1977)
Keywords: Femmes

The Neglected Majority: The Changing Role of Women in 19th Century Montreal - Cross, D. Suzanne (Histoire sociale / Social History, 1973)
Number: 12
Keywords: Femmes

The Geography of Prostitution in an Early Nineteenth-Century Urban Centre: Montreal, 1810-1842 - Poutanen, Mary Anne (Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec, 1998)
Keywords: Femmes; Prostitution

Les procès en séparation de corps dans la région de Montréal, 1795-1879 - Cliche, Marie-Aimée (Revue d'histoire de l'Amérique française, 1995)
issued: 1995-22-00
Keywords: Femmes; Mariage

Working Families: Age, Gender and Daily Survival in Industrializing Montreal - Bradbury, Bettina (Labour / Le travail, 1994)
issued: 1994-21-00
Keywords: Famille; Femmes

Les maîtresses d'écoles indépendantes: une contribution essentielle à l'éducation de la jeunesse montréalaise du premier tiers du XIXe siècle - Dufour, Andrée (Les bâtisseuses de la Cité, 1993)
Keywords: Enseignants; Femmes

Le leadership féminin dans les associations privées de charité protestantes au XIXe siècle à Montréal - Harvey, Janice (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Protestants

80 Stout and Healthy Looking Girls - Turner, Wesley (Canada - an Historical Magazine, 1975)
Number: 2
Keywords: Femmes; Irlandais

Teachers, Gender, and Bureaucratizing School Systems in Nineteenth Century Montreal and Toronto - Danylewycz, Marta; Prentice, Alison Leeds (History of Education Quarterly, 1984)
issued: 1984-21-00
Keywords: Enseignants; Femmes

The Legal Rights of Masters, Mistresses and Domestic Servants in Montreal, 1816-1829 - Hogg, Grace Laing (Université McGill, 1989)
Keywords: Domestiques; Femmes

Les domestiques en milieu urbain au début du XIXe siècle - Lacelle, Claudette (Parcs Canada, 1980)
Keywords: Domestiques; Femmes

Working Families: Age, Gender, and Daily Survival in Industrializing Montreal - Bradbury, Bettina (McClelland & Stewart, 1993)
Keywords: Famille; Femmes

"Elles ne se marièrent pas et eurent beaucoup d'enfants": analyse du discours institutionnel traitant de la mère célibataire au Québec au milieu du XXe siècle - Turcotte, Géraud (Université Laval, 1990)
Keywords: Famille; Femmes

Pigs, Cows and Boarders. Non-wage forms of Survival among Montreal Families, 1861-1881 - Bradbury, Bettina (The Challenge of Modernity: A Reader in Post-Confederation Canada, 1992)
Keywords: Famille; Femmes

Pigs, Cows, and Boarders: Non-Wage Forms of Survival among Montreal Families, 1861-91 - Bradbury, Bettina (Labour / Le travail, 1984)
issued: 1984-23-00
Keywords: Famille; Femmes

Les vocations féminines de la région montréalaise au XIXe siècle - Payette, Céline (Université du Québec à Montréal, 1991)
Keywords: Communautés religieuses; Femmes

For the Benefit of the Master: the Montreal Needle Trades During the Transition, 1820-1842 - Poutanen, Mary Anne (Université McGill, 1986)
Keywords: Apprentissage; Confection; Femmes

Debating Dower: Patriarchy, Capitalism and Widows' Rights in Lower Canada» - Bradbury, Bettina (Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec, 1998)
Keywords: Femmes; Mariage; Veuvage

Women and Wage Labour in a Period of Transition, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1987)
Keywords: Famille; Femmes; Travail

Surviving as a Widow in 19th - Century Montreal - Bradbury, Bettina (Urban History Review / Revue d'histoire urbaine, 1989)
Number: 3
Keywords: Famille; Femmes; Veuvage

Class, Culture, Family and the Law: Wife to Widow in Nineteenth-Century Quebec - Bradbury, Bettina (Programme d'études sur le Québec de l'Université McGill, 1997)
Keywords: Femmes; Mariage; Veuvage

The Evolution of the Sexual Division of Labour in Teaching: A Nineteenth-Century Ontario and Quebec Case Study - Danylewycz, Marta (Histoire sociale / Social History, 1983)
Number: 31
Keywords: Enseignants; Femmes; Travail

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Histoire sociale / Social History, 1984)
Number: 33
Keywords: Famille; Femmes; Travail

Aspects sociaux et économiques du veuvage à Montréal au milieu du 19e siècle - Favel, Valentine (Université Lumière Lyon 2, 1991)
Keywords: Famille; Femmes; Veuvage

"Against her Will and without her Consent": Women, Sexual Crimes and the Law in the District of Montreal, 1803-1843 - Ramos, Sandy (Université Concordia, 1996)
Keywords: Criminalité; Droit; Femmes

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1994)
NOTICE DG
Keywords: Famille; Femmes; Travail

Absorbing Junior: the Use of Patent Medicines as abortifacients in Nineteenth Century Montreal - Gossage, Peter (The Register, 1982)
Number: 1
Keywords: Avortement; Femmes; Médecine

Domaine des soeurs grises de Montréal - Gauthier, Raymonde (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Femmes; Patrimoine; Soeurs Grises

Prisons, Reformatories, and Convents: The Origin and Nature of Nineteenth Century Female Incarceration Facilities in Montreal - Myers, Tamara (Es Igual Pero Distinto: Essays in the Histories of Canada and Argentina, 1997)
Keywords: Criminalité; Délinquance; Femmes; Prisons

The Homeless, the Whore, the Drunkard, and the Disorderly: Contours of Female Vagrancy in the Montreal Courts, 1810-1842 - Poutanen, Mary Anne (Gendered Pasts: Historical Essays in Femininity and Masculinity in Canada, 1999)
Keywords: Délinquance; Femmes; Itinérance; Prostitution

The Development of Higher Education for Women at McGill University from 1857 to 1899 with Special Reference to the Role of Sir John William Dawson - Ronish, Donna Ann (Université McGill, 1972)
Keywords: Dawson; William; Femmes; Université McGill

History of the Montreal Ladies' Benevolent Society 1815-1920 (s.é., 1920)
Keywords: Femmes; Montreal Ladies' Benevolent Society; Philanthropie

The Women's College, with Special Reference to Royal Victoria College, McGill University - Dudkiewicz, Zina (Université McGill, 1982)
Keywords: Femmes; Royal Victoria College; Université McGill

Le Bon-Pasteur et ses oeuvres à Montréal - Gouin, Édouard (Imprimerie de l'Institution des sourds-muets, 1916)
Keywords: Communautés religieuses; Femmes; Soeurs du Bon-Pasteur

Le financement des pensionnats de jeunes filles au Québec; le modèle de la Congrégation des Soeurs de Sainte-Anne, 1850-1950 - Champagne, Lucie (Université de Sherbrooke, 1989)
Keywords: Communautés religieuses; Femmes; Soeurs de Sainte-Anne

Le financement des pensionnats de jeunes filles au Québec: le modèle de la Congrégation des Soeurs de Sainte-Anne, 1850-1950 - Dumont, Micheline; Champagne, Lucie (La Société canadienne d'histoire de l'Église catholique, sessions d'étude, 1986)
Keywords: Communautés religieuses; Femmes; Soeurs de Sainte-Anne

The Working-Class Family Economy: Montreal, 1861-1881 - Bradbury, Bettina (Université Concordia, 1984)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

Taking the Veil in Montreal, 1840-1920: An Alternative to Marriage, Motherhood and Spinsterhood - Danylewycz, Marta (Université de Toronto, 1981)
Keywords: Communautés religieuses; Congrégation de Notre-Dame; Femmes; Soeurs de Miséricorde

Profession: Religieuse. Un choix pour les Québécoises (1840-1920) - Danylewycz, Marta (Boréal, 1988)
Keywords: Communautés religieuses; Congrégation de Notre-Dame; Femmes; Soeurs de Miséricorde

Taking the Veil: An Alternative to Marriage, Motherhood, and Spinsterhood in Quebec, 1840-1920 - Danylewycz, Marta (McClelland and Stewart, 1987)
Keywords: Communautés religieuses; Congrégation de Notre-Dame; Femmes; Soeurs de Miséricorde